(untitled) (Mustansiria Dental Journal, 2023)
Backgrounds: Various information about acceptability (AT) and perceptibility thresholds (PT) for colour differences (∆E) was reviewed in dental literatures. There is consensus that determining (∆E) is ideal for identifying AT and PT. However, there is confusion about which values should be used. The aim of this review was to determine the discrepancies in research results and the critical value of ∆E. Materials and methods: MEDLINE/PubMed and Google Scholar were screened for studies that investigated colour acceptability, perceptibility, ∆E, but were not sensitive to whether only AT or PT were used. 20 studies matched the study criteria and had been included in this review and clinical measurements were made using spectrophotometers. Result: Most studies evaluated PT using approximately ∆E = 0.8–1.7. In terms of AT which ranged between 1.8 and 3.7 as a maximum. Many recent studies evaluate AT00=1.8 according to the CIE2000 colour difference formula. Conclusion: Different formulas as ∆E00 (2000) or ∆Eab(lab) in colour expression may produce different results. The CIElAB formula (ΔEab) has greater evidence; however, current research recommends the CIE2000 formula ∆E. The absence of colourimetric control has a negative effect on overall product quality.